Status of Compliance of Patient Undergoing Hemodialysis - Ballesteros-Ceneta, Ma. Lourdes; Del Rosario, Maria Shane (International Journal of Sustainability and Advanced Integrated Research, 2026)
Chronic kidney disease affects over 7 million Filipinos, with hemodialysis serving as the primary treatment modality amid limited kidney transplantation due to high costs, low organ donation rates, and infrastructure gaps, yet compliance remains challenged by psychological maladjustment, physiologic complications, and economic burdens in resource-variable private facilities. This descriptive quantitative study assessed the status of compliance to hemodialysis treatment among 46 patients from Jaime B. Berces Memorial Hospital and Dr. Amando D. Cope Memorial Hospital in Tabaco City, Albay, alongside psychological (disease acceptance, family support), physiologic (comorbidities, vascular access), and economic (income, PhilHealth coverage) correlates, using validated researcher-made questionnaires subjected to dry runs and analyzed through weighted means, frequencies, and 5-point Likert interpretations. Findings revealed very strong overall compliance (WM=4.45), led by strong physiologic adherence (WM=4.52) despite diabetes/hypertension prevalence (78%), strong psychological factors (WM=4.38) bolstered by family support, and moderate economic compliance (WM=3.85) hindered by out-of-pocket costs exceeding PhilHealth limits. Significant correlations emerged between family support (r=0.68) and session attendance, while low income predicted missed sessions; proposed measures emphasize targeted counseling, PhilHealth advocacy, and multidisciplinary care to optimize adherence and outcomes in district-level private hemodialysis units.